Becoming-policy in the Anthropocene - Gildersleeve, Ryan Evely (Education Policy Analysis Archives, 2018)
This paper takes up the theme of “Education Policy and Methodology in a Post-truth Era” by emplacing policy within the contemporary condition of the Anthropocene. The conditions of the Anthropocene demand a radical reconfiguring of policy as an apparatus for governmentality, and therefore of methodology. I intraject a potential ethical posture befitting such a reimagined becoming-policy and reconceptualized environment. The Anthropocene serves as both context and concept as the “Age of Humankind” in need of speculative and radical building and making. Drawing on prior critical policy analyses of higher education policy affecting undocumented students, I proffer plausible postures in thinking education policy and methodology that engage the contemporary moment of both “post-truth” and the Anthropocene.